A systematic review and meta‐analysis of the effects of intraoral treatments for neurogenic oropharyngeal dysphagia. (24th November 2021) - Cheng, Ivy; Sasegbon, Ayodele; Hamdy, Shaheen
Abstract: Background: Rehabilitative treatments for oropharyngeal dysphagia, including oromotor exercises and sensory stimulation, have been widely adopted into clinical practice. However, the effects of these treatments are mainly supported by exploratory studies. As such, their clinical efficacy remains uncertain. Objective: Our systematic review and meta‐analysis aimed to evaluate the efficacy of intraoral treatments for neurogenic oropharyngeal dysphagia based on evidence from randomised controlled trials (RCTs). Methods: Six electronic databases were systematically searched between January 1970 and July 2021. Data were extracted and analysed by two independent reviewers. The outcome measure was changes in (any) relevant clinical swallowing‐related characteristics. Results: Data from 285 dysphagic patients were collected from 8 RCT studies across a range of intraoral dysphagia treatments. The pooled effect size of all intraoral dysphagia treatments was non‐significant compared to control comparators (SMD [95%CI] = 0.23 [−0.22, 0.69], p  = .31; I 2  = 73%). Subgroup analysis revealed that the pooled effect sizes were also non‐significant for oromotor exercises (device‐facilitated lip resistance exercises and tongue exercises) (SMD [95%CI] = 0.11 [−0.76, 0.97]; p  = .81; I 2  = 88%) and sensory stimulation (thermal‐tactile, thermo‐chemical and electrical stimulation) (SMD [95%CI] = 0.35 [−0.03, 0.72]; p  = .07; I 2  = 0%). Conclusions: Our results showed that overall, intraoral dysphagia treatments, including oromotor exercises and sensory stimulation, do not show beneficial effects for neurogenic oropharyngeal dysphagia. The evidence for these treatments remains weak and currently inadequate to support clinical use. Large‐scale, multi‐centre RCTs are warranted to fully explore their clinical efficacy. Abstract : Our systematic review and meta‐analysis found that intraoral dysphagia treatments, including oromotor exercises and sensory stimulation, did not show beneficial effects for neurogenic oropharyngeal dysphagia. The evidence for these treatments remains weak and currently inadequate to support clinical use. Large scale, multi‐centre randomised controlled trials are warranted to fully explore their clinical efficacy.